Thermal sprayed stainless steel/carbon nanotube composite coatings - Kaewsai D. (2014)
Stainless steel/carbon nanotube (SS/CNT) composite coating was prepared by thermal spray from the feedstock powder synthesized by chemical vapor deposition at a synthesis temperature and time of 800°C and 120min under ethanol atmosphere. Microstructural investigation by TEM and SEM revealed that grown CNTs covering the surface of stainless steel particles were multi-walled type with an average diameter of about 44nm. Microstructures of pure stainless steel and SS/CNT composite coatings similarly showed splat characteristic and lamellar structure. Incorporation of CNTs was clearly observed in the composite coating. Hardness of SS/CNT composite coating (480±36 HV0.3) was higher than that of pure stainless steel coating (303±33 HV0.3). Coefficient of friction of the SS/CNT coating was almost 3 times lower than that of stainless steel coating which resulted in reduction of sliding wear rate of nearly 2 times. This research thus demonstrated a new composite coating with better wear resistive performance compared to a coating deposited by commercially available stainless steel powder. © 2010 Elsevier B.V.